Gender and ethnic inequalities in LAC countries - Carla Canelas; Silvia Salazar (IZA Journal of Labor & Development, 2014)
This article examines the structure of gender and ethnic wage gaps and the distribution of both paid and unpaid work in LAC countries. Its main contribution is to expose the double discrimination endured by women in the region. Indeed, the results indicate that women are highly discriminated in the job market and undertake most of the domestic activities in the household, allocating in average 40 hours per week to paid market activities and another 40 hours to in-home unpaid activities. The indigenous population also suffers from discrimination, but the wage gap is mainly explained by the difference in endowments, highlighting their limited access to education and their concentration in rural areas. The wage quantile decomposition results suggest the presence of sticky floor effects for both women and indigenous workers.
Keywords: J22; J31; J71; 330; Inequality; Ethnicity; Gender; Time-use